A construção social do problema ambiental: mobilização e ação coletiva a partir da APA do Itapiracó em São Luís- MA - BAYMA, Joallysson Desterro (2022)
The present work analyzes the connection between society and nature from the relations of social uses and transformations of the place. From this perspective, it investigates the social formation of the environmental problem from actors and their involvement with the Itapiracó Protection Area, a place of environmental conservation present in the urban space of the city of São Luís. It describes the process of formation of the APA of Itapiracó and the relations of use that the residents of the interior and surroundings make of the place, in this process it was tried to evidence the connection with the urban context and some of the perspectives involved in its changes. Reflexively, one can perceive the social elaboration of an environmental problem related to this place of nature, mobilized from collective actions and the formation of a movement in defense of the APA. The actors involved in this process form discursive elaborations and characterize the problems observed in this unit as part of a public demand of an environmental nature. In this way, these actors establish the link between use, affectivity, memories, symbolic and conservation practices to highlight the relevance of the APA to their neighborhoods and their experience. The analysis was developed from a theoretical review of the appropriate categories for the work, data collection on the conservation unit, direct observation, semi-structured interviews with members of the APA-related movement, actors linked to the unit's management and residents. The study evidences the formation of an environmental problem from a place, and the intertwined relationships so that a demand becomes public.